Koperasi dalam Perpektif Hukum Islam - Zia Ulkausar Mukhlis (Jurnal Kawakib, 2021)
Cooperatives are business entities established by individuals or groups to improve the economic quality of the community. Especially in Indonesia, cooperatives have played their role since pre-independence. One of the functions of cooperatives is as a fund-crediting agency. With the development of cooperatives in Indonesia and the high awareness of the Indonesian people about Islamic law in every transaction in order to avoid what is called usury and gharar (losses) make cooperatives interesting to study more deeply using the lens of Islamic law. It is judged that cooperatives are a new type of transaction that did not occur in the days of the prophets and scholars of previous schools of thought. It is interesting because the ulama have different views on cooperatives. Of course, the difference is not only in terms of texts but also from the harm and benefits of cooperatives. Keywords: Cooperatives, Transactions, Islamic Law Koperasi merupakan badan usaha yang didirikan oleh individu atau kelompok guna meningkatkan kualitias ekonomi masyarakat. Terkhusus di Indonesia koperasi telah memainkan perannya sejak pra kemerdekaan. Salah satu fungsi koperasi adalah sebagai badan pengkreditan dana. Dengan berkembangnya koperasi di Indonesia serta tingginya kesadaran masyarakat Indonesia akan hukum Islam dalam setiap transaksi agar terhindar dari yang namanya riba dan gharar (kerugian) menjadikan koperasi menarik untuk dikaji lebih dalam menggunakan kaca mata hukum Islam. Dinilai karena koperasi termasuk jenis transaksi baru yang tidak terjadi di zaman nabi dan ulama mazhab terdahulu. Menjadi menarik karena ulama berbeda pendapat dalam memandang koperasi. Tentu perbedaan itu bukan ditinjau dari nash saja melainkan dari mudharat dan manfaat yang ditimbulkan koperasi. Kata Kunci: Koperasi, Transaksi, Hukum Islam